Deciphering the role of the lncRNA TRIBAL in hepatocyte models - Sébastien Soubeyrand; Paulina Lau; Ruth McPherson (PLoS ONE, 2025)
We recently reported that the long non-coding RNA TRIBAL /TRIB1AL was required to sustain key hepatocyte functions. Here, we identify HepaRG cells as a model for studying TRIBAL and provide additional validation and functional insights. In contrast to HepG2 and HuH-7 cells, differentiated HepaRG cells showed similarities to primary hepatocytes in response to TRIBAL suppression. TRIBAL suppression was associated with reduced HNF4A and MLXIPL abundance in hepatocytes and HepaRG cells. TRIBAL targeting using a panel of cognate antisense oligonucleotides confirmed specificity. A comparison of TRIBAL -suppressed hepatocyte and HepaRG transcriptomics identified extensive functional overlap. Biological ontologies associated with key hepatic metabolic functions were predicted to be inhibited in both models. Comparative analyses with TRIB1 -suppressed HepaRG cells, a central metabolic regulator vicinal to TRIBAL , also revealed extensive functional congruence with TRIBAL . Interestingly, TRIBAL transduction failed to restore function in TRIBAL -suppressed cells, which may be linked to structural differences, as supported by contrasting RNAse R sensitivities between the endogenous and transduced forms. In summary, these findings support the use of HepaRG cells as an experimental model to study TRIBAL and underscore its importance in regulating key hepatocyte genes essential for metabolic function.